Prediction the Maximum Deflection of the Prototype of Nailed-slab Pavement System Using the Allowable Equivalent Modulus of Subgrade Reaction - Puri, Anas; Oktavia, Ferly; Elizar; Dharmowijoyo, Dimas B.E.; Ali, Mujahid; Liza Evianti Tanjung (UIR PRESS, 2025)
An equivalent modulus of subgrade reaction was proposed for analyzing the Nailed-slab Pavement System. This modulus is defined by accumulating the modulus of subgrade of the slab and the additional modulus of subgrade reaction which is contributed by a pile under the slab. The additional modulus can be defined by the Modified Hardiyatmo Method. The equivalent modulus of subgrade reaction only consideres a safety factor for additional modulus of subgrade reaction. In this research, a global safety factor will be considered for all modulus. This research is aimed to learn the prediction of the slab deflection by using the allowable equivalent modulus of subgrade reaction. The global safety factor was varied by 1.0; 2.0; 2.5; and 3.0. The slab deflection was calculated by using Beam on Elastic Foundation. Data of the nailed-slab and the soil were based on the previous researcher for a single pile nailed-slab model. Results show that the calculated deflection of the slab was in good agreement with the observed deflection. Increasing the global safety factor resulted in the over-estimated slab deflections. It means the design by using allowable equivalent modulus of subgrade reaction tends to result in a safety zone.